Legal Protection For Mutual Fund Investors At PT AJ Central Asia Raya (CAR Life Insurance) Palembang, South Sumatra, In The Event Of Losses - Sherinda, Ghea Premarsha; Erniwati, Erniwati; Agustina, Sakinah (JURNAL HUKUM SEHASEN, 2025)
This study aims to analyze the legal responsibility of mutual fund organizers at PT. AJ Central Asia Raya (CAR Life Insurance) in Palembang City for losses experienced by investors. A mutual fund is a vehicle for collecting funds from investors to be managed in an investment portfolio by an investment manager. In practice, investor losses often raise legal questions regarding the organizer’s responsibilities. This study employs a normative juridical method using statutory and case study approaches. The findings indicate that mutual fund organizers are obligated to protect investors' interests in accordance with Law Number 8 of 1995 concerning Capital Markets and the regulations of the Financial Services Authority (OJK). If losses occur due to negligence or mismanagement, organizers may be held legally accountable and subject to administrative, civil, or criminal sanctions. The case at PT. AJ Central Asia Raya highlights the importance of increased supervision and accountability in mutual fund management. The study recommends stronger regulatory enforcement and oversight by OJK, along with greater transparency and investor education. These measures are essential to ensure effective legal protection for investors and to maintain public confidence in the mutual fund industry.